Efektivní marketingová komunikace na veletrzích - Fusková, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Diplomová práce je zpracována pro společnost TONDACH Česká republika, s. r. o. Je zaměřena na efektivní marketingovou komunikaci na veletrzích. Obsahuje informace o efektivním využití prezentace firmy na veletrzích. Možnosti a návrhy, jak by mohla vypadat struktura prezentace firmy na jednotlivých veletrzích. Na co by se měla firma zaměřit, co využít, aby byl veletrh pro firmu efektivní.

The master´s thesis is prepared for the company TONDACH Czech Republic, Ltd. is focused on effective marketing communications at fairs. It contains information on the efficient use of company presentation at trade fairs. Options and proposals on how it could look like the structure of company presentations on various trade fairs. What should the company focus on what used to be fair for the company effectively.
Effective Marketing Communication on Fairs
Keywords: veletrhy a výstavy; reklama; soutěže a slevy; doprovodný program; fairs and exhibitions; advertising; competitions and discounts; accompanying program